CONCEIVE-DESIGN-IMPLEMENT-OPERATE (CDIO) INNOVATIVE TEACHING METHODS IN REAL ESTATE EDUCATION - Mat Noor, Noorsidi Aizuddin; Diana Deris, Farhana; Omar, Mustafa; Abdul Hamid, Hamdi; Mokhtar, Afizan (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2024)
ABSTRAK The presented research aims to investigate the impact of the CDIO framework on changing the existing learning-teaching paradigm in real estate education in Malaysia to improve learning engagement and students’ critical thinking skills. On this note, the use of traditional teaching approaches that involve lectures in real estate education is found to be lacking in meeting the needs of the dynamic market, therefore calling for innovation. This research uses quantitative and qualitative data from 150 students from three universities: pre and post intervention questionnaires, focus group discussions, and class observations. The studies reveal that after intervention, the extent of students’ participation increased from 35% to 75%, and there are improvements in students’ critical thinking skills; the average scores from pre-tests of 60% rose to 80% post-tests. From the students’ perspective, CDIO promoted meaningful learning based on project-centred learning activities done in a contextual manner, improving the perceived relevancy of learning activities. Therefore, the present research substantiates that CDIO methodologies integrate practice and research to positively transform student learning experiences, activity levels, and critical analysis, strongly advocating for real estate educational reform in the Malaysian context. It means the focus on project-based active learning prepares students to solve actual problems that affect them and brings education and skills in line with the requirements of the given sphere. Based on the findings of this study, the following recommendations should be made for future research: The effectiveness of CDIO integration and its long-term implications should be investigated. Broader implications point to the idea that implementing CDIO-inspired approaches provides a workforce that is more competent and better synchronised, which is imperative in a continuously transforming real estate market within Malaysia and other states.